2017
DOI: 10.5505/tjtes.2017.99894
|View full text |Cite
|
Sign up to set email alerts
|

CT Findings of Primary Epiploic Appendagitis as an Easily Misdiagnosed Entity

Abstract: BACKGROUND: Primer epiploic appendagitis (PEA) is an uncommon condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…The term "epiploic appendagitis" was initially described in 1956 by Lynn et al, and its computed tomography (CT) features were described for the first time in 1986 by Danielson et al [12,[14][15][16]. e179 © Pol J Radiol 2020; 85: e178-e182…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The term "epiploic appendagitis" was initially described in 1956 by Lynn et al, and its computed tomography (CT) features were described for the first time in 1986 by Danielson et al [12,[14][15][16]. e179 © Pol J Radiol 2020; 85: e178-e182…”
Section: Introductionmentioning
confidence: 99%
“…EA can be primary or secondary. Primary EA is an inflammatory disease that may arise from a spontaneous torsion causing obstruction of blood flow within the omental appendage, then ischaemia up to a necrosis, or from spontaneous thrombosis of the draining vein and inflammation [13,15,21]. Instead, secondary EA may arise from adjacent inflammatory diseases involving the colonic wall and surrounding mesocolon, such as diverticulitis or appendicitis [1,12].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical presentation may vary among patients. This condition is often an underestimated and overlooked mimicker, easily misdiagnosed with other causes of abdominal pain requiring urgent care or surgical evaluation in emergency department, particularly acute diverticulitis (left iliac pain) or acute appendicitis (right iliac pain) [ 10 , 12 , 19 ]. On physical examination, patients complain of focal non-migratory abdominal pain in the lower abdominal quadrants (left more commonly than right), not exacerbated by physical movement, without significant guarding or rigidity, and in the absence of a palpable mass [ 10 , 11 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pain is typically circumscribed and the patient may often point his finger on the place where the lesion is situated. Patients may also report postprandial fullness, swelling, vomiting, early satiety, diarrhea, and rarely mild fever [ 10 , 12 , 14 , 18 , 20 , 21 ]. White blood cell count, erythrocyte sedimentation rate, and C-reactive protein levels are within normal range in the majority of patients, while mild leukocytosis may occasionally be observed due to inflammatory response [ 10 12 , 14 , 20 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“… 4 In a study of 45 patients with EA, a presumptive clinical diagnosis was acute appendicitis (n=13), acute cholecystitis (n=2), acute diverticulitis (n=19), renal colic (n=7) and ovarian pathology (n=4). 7 Obesity is the only identifiable risk factor associated with EA. 1 2 8 A retrospective CT study of 100 patients with EA versus 100 patients with acute abdomen demonstrated significantly greater abdominal adipose volume, visceral adipose area and subcutaneous adipose area in the EA group.…”
Section: Introductionmentioning
confidence: 99%